Contraception and birth control: bioethical focus (Saúde Ética & Justiça, 2010)
The following article composes a discussion about the contraception issue. The author presents ideasexplaining why birth control is needed and refutes arguments against contraception as those which claim that it is something wrong because it is artificial or unnatural.